Políticas de inclusão de pessoas com deficiência à luz de uma abordagem argumentativa: um estudo de caso da UFLA - Dias, Georgina Amélia de Oliveira (2022)
When it comes to the student field, universities are seen as a model environment for the development of practices, where the individual who lives in community can guarantee an experience with dignity. Inclusion, however, still requires an effort to ensure that the academic universe effectively applies teaching to all with equity of conditions and possibility of learning, which meet all kinds of educational needs. This research aims to analyze the perceptions of the actors involved about inclusive education policies at the university, focusing on the political contexts and role of the university in this context. Eight students were interviewed in January 2022 and the qualitative analysis model was used and the content was analyzed following Bardin's methodology from the transcription of the material. As a general result, it was possible to realize that despite the technologies and assistance given by PADNEE, adjustments are still needed regarding these issues as well as community involvement in the inclusion actions proposed by the institution. At the end of the study, it is possible to verify that the educational inclusion of people with disabilities in higher education is still a challenge, verifying, mainly, the lack of preparation of teachers to deal with the different educational needs presented by the students. Infrastructure and community awareness of the process have also been verified as challenges.